Evaluasi Kondisi Eksisting Timbulan Sampah Berdasarkan Jumlah Penduduk dan Kepadatan Penduduk di Kota Batam - Messal Veronica; Prajati, Gita (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Universal, 2024)
Population and population density affect the production of waste generated. The increasing of population and population density in Batam caused by the economic growth. The development of Batam not only led into the increasing of population but also waste generated. Therefore, the aims of this research is to evaluate the existing condition of waste generated based on population and population density in Batam with descriptive analysis. Descriptive statistical analysis was conducted in order to know range value, mean and standard deviation of waste generated, population and population density. The result shows waste generated in Batam has increased into 4.81% from 2021 to 2022. Batam Centre District supplies the most amount waste generated (23%), whereas Nongsa District supplies the less amount of waste generated (4,86%). The Daily waste generation rate in Lubuk Baja is higher than daily waste generated based on SNI. Another specific variable in population might be given impact to waste generated, which is ratio comparation of population based on gender. Descriptive analysis’s result stated that waste generated has range value 12,478,650 – 60,336.220 with standard deviation 14,542,363.712 and mean 28,998,778.89. Population range value is 61,497–226,040 with standard deviation and mean respectively 57,227.43 dan 135,304.22. Last, population density has range value 295 – 6,406 with standard deviation 1,907.59 and mean 2,550.89.